축열 성능 향상 SSPCM 혼합 콘크리트 제조 및 열적특성 분석 - 정수광(Jeong Su-Gwang); 장성진(Chang Seong Jin); 임재한(Lim Jae-Han); 김희선(Kim Hee-Sun); 류성룡(Ryu Seong-Ryong); 김수민(Kim Sumin) (한국태양에너지학회 논문집, 2015)
n-octadecnae based shape stabilized phase change material (SSPCM) was prepared by using vacuum impregnation method. And an exfoliated graphite nanoplate (xGnP) which has high thermal conductivity properties is used as a PCM container. And then we made heat storage concretes which contains SSPCM for reducing heating and cooling load in buildings. In the prepararion process, the SSPCM was mixed to a concrete as 10, 20 and 30wt% of cement weight. The thermal properties and chemical properties of heat storage concrete were analyzed from Scanning electron microscope (SEM), Fourier transformation infrared spectrophotometer (FT-IR), Deferential scanning calorimeter (DSC), Thermogravimetric analysis (TGA) and TCi thermal conductivity analyzer. And we conducted surface temperature analysis of SSPCM and xGnP by using heat plate and insulation mold.